PENGARUH MEDIA E-COMIC MATERI ARITMATIKA SOSIAL TERHADAP MINAT BELAJAR SISWA SMP - Hendrikus Andre; Yulis Jamiah; Mohamad Rif'at (TRANSFORMASI, 2023)
The lack of interest in student learning can occur, one of which is because the teacher lacks variety in the use of media in the learning process in the classroom. This can happen because of the lack of knowledge about various media that can be used in learning. This study aims to describe the results of the application of e-comic media to social arithmetic material, and to determine the influence of the media on junior high school students' learning interest. This study uses a quantitative approach with the type of research that is pre-experimental with a one group pre test-post test design, which consists of the independent variable (e-comic social arithmetic material) and the dependent variable (student learning interest). The research sample was 43 students who had received social arithmetic material at SMP LKIA Pontianak. The data collection instrument is a questionnaire. Data were analyzed by descriptive analysis and inferential analysis. Based on the results of student responses, it was found that the application of e-comic media for social arithmetic material was classified as very good and the results of the hypothesis test stated that there was an effect of using e-comic media for social arithmetic material on students’ learning interest at SMP LKIA Pontianak.